Type 1 Diabetes Mellitus and COVID-19 - Asadipooya, Kamyar; Bu, Pengli (Archives of Clinical and Medical Case Reports, 2024)
Type 1 diabetes mellitus (T1DM) accounts for around 5-10% of all diagnosed cases of diabetes. It is caused by lack of insulin production, typically secondary to autoimmune destruction of pancreatic β-cell. The exact mechanisms and etiologies are not entirely revealed, but it is thought that genes and environmental factors, such as viruses, might trigger autoimmunity against the pancreas.